Kajian Hidrostratigrafi Bentanglahan Kepesisiran Tipologi Marine Deposition Coast Kecamatan Ngambur Provinsi Lampung - khoirullah, evi mivtahul; Setyawan Purnama, I.g.L.; Widyastuti , Margaretha (Pendidikan Geografi Fakultas Keguruan dan Ilmu Pendidikan Universitas Mulawarman, 2021)
This research was conducted on coastal area located in Ngambur Subdistrict, Pesisir Barat Regency, Lampung Province. Geomorphologically, typology of this coastal area formed of marine deposition coast. Which is consist of sandy beach (M1), beach ridge (M2), and fluviomarine (Fm). The purpose of this reasearch is to reconstruct and analyze charactreistic of hydrostratigraphy which is includes of soil stratigraphy system and properties, and physical properties of groundwater in the research area. Vertical distribution of soil resistivity obtained by measuring 24 of measuring points with depth of penetration’s up to 150 meters. Determination of measurement points are selected using purposive sampling method. Furthermore, the resistivity value of the measurement results is calculated using IP2Win software. Results of the calculation matched with soil resistivity tables. Results of the research show that vertically the type of aquifers identified are aquifer, aquitard, and aquifug. The constituent material is dominated by alluvium containing fresh groundwater which acts as an aquifer and sandstone materials which acts as aquitard. The electrical conductivity value (DHL) measured <1,200mmhos / cm which indicates that the groundwater in ths area is classified as fresh groundwater.